1995
DOI: 10.1016/0092-8674(95)90038-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nef allele that causes lymphocyte activation and acute disease in Macaque monkeys

Abstract: Residues 17 and 18 in nef of SIVmac239 were changed from RQ to YE to create a translated sequence of SRPSGDLYERLLRARGETYGRLLGEVEDGYSQSP from residues 10-43. The YXXL motifs in this context match very well with consensus sequences for SH2 binding domains and are similar to ones present in nef of the acutely lethal pathogen SIVpbj14. The YE variant of SIVmac239, unlike SIVmac239 but like SIVpbj14, replicated well in resting peripheral blood mononuclear cell cultures, caused extensive T lymphocyte activation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
240
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(248 citation statements)
references
References 36 publications
5
240
3
Order By: Relevance
“…Among the regulatory proteins is Nef, whose role in viral infection and disease progression has been controversial (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Among the putative functions attributed to Nef are the maintenance of high viral load (1) and immune evasion due to its down-regulation of CD4 (2) and MHC I molecules (7).…”
Section: Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the regulatory proteins is Nef, whose role in viral infection and disease progression has been controversial (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Among the putative functions attributed to Nef are the maintenance of high viral load (1) and immune evasion due to its down-regulation of CD4 (2) and MHC I molecules (7).…”
Section: Hivmentioning
confidence: 99%
“…Briefly, 3 ϫ 10 5 Jurkat cells or primary CD4ϩ T cells suspended in 300 l of migration medium (RPMI ϩ 0.5% bovine serum albumin) were loaded into each Transwell filter. Filters were then transferred to another well containing 600 l of migration medium with the indicated concentrations of SDF-1␣.…”
Section: Creation and Maintenance Of Permanent Nef-expressing T Cellmentioning
confidence: 99%
“…However, numerous controversial findings have been reported. For instance, in some in vitro studies, Nef was found to induce T-cell activation (1,3,5,6,15,16,37,55,68), while in others it was reported to inhibit (2,3,11,13,20,30,38,45,46) T-cell activation. Such conflicting results suggest that the function of Nef, particularly in vitro, may be difficult to fully appreciate.…”
mentioning
confidence: 99%
“…Based on numerous observations, Nef appears to play a multifaceted role; it was found to promote high virulence and accelerate viral replication (reviewed in reference 26) and to downregulate cell surface CD4 (47,61) and major histocompatibility complex class I (MHC-I) (35) molecules, as well as to affect T-cell activation (1,3,15,38,62), proliferation (12,36), and cytokine (interleukin-2 [IL-2] and IL-10) production (7,38,67). However, numerous controversial findings have been reported.…”
mentioning
confidence: 99%
“…It is possible that other nonconservative changes of Leu 64 also promote the pro-apoptotic potential of Vpr. This result is reminiscent of SIVmac239 Nef, which upon acquiring two point mutations promotes efficient viral replication in resting cells (24). Although mutations occur frequently during HIV-1 infection, Leu 64 mutations are rarely observed (Table I).…”
Section: Discussionmentioning
confidence: 99%